(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: The environment of hospital can be one of the sources of hospital infections. Good environmental hygiene practices in hospitals help ensure the safety of patients and medical staff in medical examination and treatment activities. Objectives: Describe the knowledge and practice of environmental sanitation of medical staff at the National Eye Hospital and analyze some related factors. Methods: Cross-sectional survey, quantitative research. Results: This study collected information from 323 health workers (NVYT), National Eye Hospital through questionnaires and observation using checklists. The research results show that the knowledge and practice of environmental sanitation in the control of hospital-acquired infections of health workers is quite good. Conclusion: The rate of health workers with knowledge of environmental sanitation reached 70,6%. The rate of health workers with practices of environmental sanitation reached over 75%. There are 4 factors related to knowledge including: age, working position, working time and professional qualifications. Three factors related to practices including: Gender, working position and time of training on infection control (p<0.05).